Unilateral perivertebral fibrosis associated with lordosis, kyphosis and scoliosis (LKS) in farmed Chinook salmon in New Zealand. - Munday JS; Perrott MR; Symonds JE; Walker SP; Lovett B; Preece MA; Davie PS (My University)
Vertebral column lordosis, kyphosis and scoliosis (LKS) can result in downgrading of farmed Chinook salmon Oncorhynchus tshawytscha in New Zealand. No cause of LKS has been identified. Radiography and histology were used to quantify LKS and perivertebral fibrosis in 27 fish with LKS visible at harvest and 30 visually normal fish from 3 New Zealand farms. Radiographic LKS was present in all 27 fish with LKS and in 18 of 30 fish without visible LKS. Quantification of the radiographic severity revealed significantly higher radiographic severity scores in fish with visible LKS (mean ± SD = 5.89 ± 2.41) than in fish with no visible, but radiographic LKS (1.44 ± 0.86, p < 0.001). The most frequent histological finding was unilateral perivertebral fibrosis that often extended into the horizontal septum and adjacent myomeres resulting in separation or loss of myocytes. Fibrosis was visible in all fish with LKS and in 12 of 30 fish without visible LKS. Fibrosis scores were higher in fish with visible LKS (3.32 ± 1.71) than in fish without visible LKS (0.35 ± 0.57, p < 0.001). The radiographic LKS severity scores were significantly correlated to the fibrosis scores (R2 = 0.59 p < 0.001) in the fish. Histology of other tissues revealed multifocal inflammation within muscle, peripheral connective tissues and myocardium which were considered most likely incidental in these fish. In this study, LKS was consistently and significantly associated with perivertebral fibrosis, suggesting that perivertebral fibrosis is an important process in the development of LKS. Further research to determine the cause of the fibrosis is required.
Keywords: Oncorhynchus tshawytscha; Spinal curvature; Aquaculture; Histopathology; Inflammation; Pathogenesis; Salmonid; 06 Biological Sciences; 07 Agricultural and Veterinary Sciences